Juan Jose Marin et al. Popular Cultures and Public Policies in Mexico and Central America (XIX and XX centuries) Alajuela: Museo Histórico Cultural Juan Santamaría 2002 - Silva H., Ana Margarita (Revista de historia., 2002)
This book is a memory constituted by eleven of the papers presented at the Seminar "Popular Cultures and Public Policies in Mexico and Central America (XIX and XX centuries)", held at the Juan Santamaría Historical Cultural Museum, in the city of Alajuela, Costa Rica, between September 20 and 22, 2000.